Measuring direct current trans-epithelial electrical resistance in organ-on-a-chip microsystems. Issue 3 (27th November 2014) - Odijk, Mathieu; van der Meer, Andries D.; Levner, Daniel; Kim, Hyun Jung; van der Helm, Marinke W.; Segerink, Loes I.; Frimat, Jean-Phillipe; Hamilton, Geraldine A.; Ingber, Donald E.; van den Berg, Albert
Abstract : TEER measurements are ideal for characterizing tissue barrier function in organs-on-chip studies for drug testing and investigation of human disease models; however, published reports indicate highly conflicting results even with identical cell lines and setups. Abstract : Trans-epithelial electrical resistance (TEER) measurements are widely used as real-time, non-destructive, and label-free measurements of epithelial and endothelial barrier function. TEER measurements are ideal for characterizing tissue barrier function in organs-on-chip studies for drug testing and investigation of human disease models; however, published reports using this technique have reported highly conflicting results even with identical cell lines and experimental setups. The differences are even more dramatic when comparing measurements in conventional Transwell systems with those obtained in microfluidic systems. Our goal in this work was therefore to enhance the fidelity of TEER measurements in microfluidic organs-on-chips, specifically using direct current (DC) measurements of TEER, as this is the most widely used method reported in the literature. Here we present a mathematical model that accounts for differences measured in TEER between microfluidic chips and Transwell systems, which arise from differences in device geometry. The model is validated by comparing TEER measurements obtained in a microfluidic gut-on-a-chip device versus in a Transwell culture system. Moreover, we show that even small gaps in cell coverage ( e.g., 0.4%) are sufficient to cause a significant ( 80%) drop in TEER. Importantly, these findings demonstrate that TEER measurements obtained in microfluidic systems, such as organs-on-chips, require special consideration, specifically when results are to be compared with measurements obtained from Transwell systems.